Akurasi Kadar Lysophosphatidic Acid Plasma dan Ca125 Serum Penderita Tumor Ovarium Jenis Epitel untuk Prediktor Keganasan Ovarium - APRILIAWAN, TRI; ASKANDAR, BRAHMANA (Indonesian Journal of Cancer, 2014)
This study was conducted to determine and compare the sensitivity, specificity, positive predictive value and negative predictive value between CA125, Lysophosphatidic Acid Plasma (LPA) and combination of LPA - CA125 in patients with ovarian mass.This study was a analytic observational cross sectional studies, with 56 subjects who had ovarian tumors, who had the inclusion and exclusion criteria research, in Department of Obstetrics and Gynecology FK-Unair/dr. Soetomo Hospital, Surabaya. After that, patients performed surgery, and histopatology examination of operation specimens in this hospital. Inclusion criteria for this study were patients with epithelial ovarian tumors from Anatomical Pathology examination. The 56 study subjects , we were divided into 2 groups based on histopatological examination, one group with 31 subjects we classified into epithelial type malignant ovarian tumors study group, while the other group consist of 25 subjects we classified into epithelial type benign ovarian tumors study group.Sensitivity, specificity, positive predictive value, negative predictive value of CA125 was 87.1%; 28%; 60%; and 63.8%. Sensitivity, specificity, positive predictive value, negative predictive value LPA was 51.6%; 76%; 72.7%; and 55,9%. And sensitivity, specificity, positive predictive value, negative predictive value combination LPA - CA125 was 45.2%; 92%; 87.5%; and 57.5%. And in this study we get the CA125 cut-off at 50 u/mL gives better results than 35 u/mL, whereas the LPA cut-off 2.5 ?M still the best, although the Kappa analysis results for both are not significant.In this study, plasma LPA level patients with ovarian tumor can not be used as a tumor marker for epithelial malignant ovarian cancer. CA125 levels can be used as a tumor marker for epithelial malignant ovarian cancer, while combination of CA125 levels and LPA levels increase the specificity but does not increase the sensitivity. This was contrast with previous studies that the sensitivity and specificity of plasma LPA is excellent and they proposed use LPA plasma as a tumor marker.